A scalable 32 channel neural recording and real-time FPGA based spike sorting system - Williams,I; Luan,S; Jackson,A; Constandinou,TG (IEEE, 2015)
This demo presents a scalable a 32-channel neuralrecording platform with real-time, on-node spike sorting ca-pability. The hardware consists of: an Intan RHD2132 neuralamplifier; a low power Igloo ® nano FPGA; and an FX3 USB3.0 controller. Graphical User Interfaces for controlling thesystem, displaying real-time data, and template generation witha modified form of WaveClus are demonstrated.